Development of an intervention (PICASO) to optimise the palliative care capacity of social workers in Flanders: a study protocol based on phase I of the Medical Research Council framework. Issue 10 (11th October 2022) - Taels, Brent; Hermans, Kirsten; Van Audenhove, Chantal; Cohen, Joachim; Hermans, Koen; Declercq, Anja
Abstract : Introduction: An important challenge for future palliative care delivery is the growing number of people with palliative care needs compared with the limited qualified professional workforce. Existing but underused professional potential can further be optimised. This is certainly the case for social work, a profession that fits well in multidisciplinary palliative care practice but whose capacities remain underused. This study aims to optimise the palliative care capacity of social workers in Flanders (Belgium) by the development of a Palliative Care Program for Social Work (PICASO). Methods and analysis: This protocol paper covers the steps of the development of PICASO, which are based on phase I of the Medical Research Council framework. However, additional steps were added to the original framework to include more opportunities for stakeholder involvement. The development of PICASO follows an iterative approach. First, we will identify existing evidence by reviewing the international literature and describe the problem by conducting quantitative and qualitative research among Flemish social workers. Second, we will further examine practice and identify an appropriate intervention theory by means of expert panels. Third, the process and outcomes will be depicted in a logic model. Ethics and dissemination: Ethical approval for this study was given by the KU Leuven Social and Societal Ethics Committee (SMEC) on 14 April 2021 (reference number: G-2020-2247-R2(MIN)). Findings will be disseminated through professional networks, conference presentations and publications in scientific journals.